Photorealistic 3D Rendering of Furniture Implementation of Tools for Modeling, Shading and Rendering - Hellsten, Sven; Larsson, Jakob; McEvoy, Peter; Nelson, Vidar; Olausson, Victor; Solin, Jonatan (My University, 2016)
Photorealistic 3D rendering of product images is successfully used by companies such as IKEA Communications AB. However, there are still problems where the current methods fall short. We investigate three such problems. First, we develop a tool for the 3D-modelling of woven rattan furniture. The resulting tool alleviates some of the work involved in creating detailed 3D models of rattan furniture by automatically generating an interwoven structure of strands. The tool falls short when attempting to create a heavily curved rattan mesh. Second, we implement a physically based shading model for woven cloth. The implemented shader can accurately simulate the appearance of certain types of woven cloth. Fabrics featuring more variation in structure prove difficult to recreate using this model. Finally, we develop a ray tracing renderer which uses hardware acceleration for the creation of images at interactive rates. This results in a tool which can preview scenes featuring complex objects and different materials, and serves as a proof-of-concept for utilizing hardware acceleration for ray tracing.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science